Risk Management Practices and Financial Stability in Conventional Commercial Banks: A Systematic Literature Review of Scopus Q1–Q2 Articles (2019–2024) - Khairil Anwar (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study provides a systematic literature review of empirical and theoretical research examining the relationship between risk management practices and financial stability in conventional commercial banks. Using the PRISMA methodology, the review synthesizes evidence from more than 100 peer-reviewed articles published in Scopus-indexed Q1–Q2 journals between 2019 and 2024. The review focuses exclusively on conventional commercial banks and analyzes how different categories of risk—credit, liquidity, market, operational, and systemic risk—are managed within contemporary regulatory and governance frameworks.The findings indicate that credit and liquidity risks remain the dominant sources of bank fragility, particularly during periods of macroeconomic stress. Empirical evidence consistently shows that effective credit risk controls and adequate liquidity buffers enhance bank-level resilience, although the magnitude of their stabilizing effects varies across institutional and regional contexts. The review further highlights the growing importance of Enterprise Risk Management (ERM) and Basel III regulatory instruments, including capital buffers and stress testing, in mitigating excessive risk-taking and strengthening shock absorption capacity. However, the effectiveness of these mechanisms is not uniform, as differences in governance quality, market structure, and regulatory enforcement shape risk outcomes. At the systemic level, the literature suggests that well-capitalized banks with integrated risk governance contribute to overall financial stability by reducing contagion risk and supporting credit provision during crises. Nonetheless, several gaps remain, particularly regarding the interaction between risk culture, technological risk, and macroprudential policy effectiveness in emerging markets. By critically synthesizing recent high-quality evidence, this review contributes to the banking and financial stability literature and offers policy-relevant insights for regulators and bank managers seeking to enhance the resilience of conventional commercial banking systems.